EFEKTIVITAS STEAM EJECTOR TINGKAT PERTAMA DI PLTP LAHENDONG UNIT 2 - Brian Deril Kemur; Frans Palobo Sappu; Hengky Luntungan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
ABSTRACT First stage steam ejector is a part of the gas extraction system at PLTP Lahendong Unit 2 with the main function to remove non-condensable gas (NCG) collected in the main condenser continuously in order to keep the main condenser vacuum. The research aim is to determine the ability of the steam ejector actual conditions in ejecting NCG from the main condenser. Computational fluid dynamics simulations is used to analyze the flow characteristics in the steam ejector. Simulation is done by comparing the actual conditions and the factory design condition of first stage steam ejectors. Simulation resulting in the efficiency of steam ejector actual condition is 0,527 while factory design condition is 0,554, meaning there is a decrease in the efficiency by 4,87%. The simulation results show the ability of steam ejectors actual condition to eject the NCG from the main condenser is 1.402,11 kg/hr and for steam ejector factory design is 1.479,34 kg/hr. The ability of the steam ejector actual conditions is decreased by 5,22% from the steam ejector factory design conditions. Keywords: Steam Ejector, NCG, Efficiency.